Pelatihan dan Pendampingan Penggunaan Media Pembelajaraan Berbasis Multi Media pada Guru-Guru Sejarah SMA Negeri 4 Ambon - Touwe, Sem; Ufie, Agustinus; Pattiasina, Johan; Ima, Wa (Universitas Pattimura, 2025)
Community service activities in the form of mentoring for learning media development aim to enhance teachers' knowledge and skills in creating effective, computer-based instructional materials. This initiative targets teachers at SMA 4 Ambon City and is designed to improve teaching creativity and support effective learning management. The mentoring process involves a combination of lectures, demonstrations, hands-on practice, and interactive Q&A sessions. Lectures focus on the concepts of professional teaching and the role of creativity in education, while demonstrations present the stages of developing learning media. Participants then engage in practical sessions to design their own media tailored to the subjects they teach. The Q&A segment provides space for teachers to address challenges encountered during the development process. As a result, participants are expected to be able to design and produce relevant, engaging learning media that meets curricular needs and boosts classroom effectiveness, ultimately enhancing their overall teaching performance.